Addressing Fall Risk From the Emergency Department: What Are We Missing?. (January 2021) - Hill, April; Evans, Dian Dowling
Abstract : The Research to Practice column focuses on improving the research critique skills of emergency nurses and advanced practice providers to assist with the translation of research into practice. In this issue, we discuss the findings of a secondary data analysis conducted by K. Davenport, M. Alazemi, J. Sri-On, and S. Liu (2020) that examined emergency department provider identification of modifiable risk factors when assessing older adults who present after a fall. The results found that providers frequently miss identifying and intervening in modifiable risk factors that contribute to adverse outcomes and readmissions following discharge. The results suggest future research needs and have implications for emergency nurse practitioner educational preparation.